Mitochondrial encephalomyopathy: variable clinical expression within a single kindred. Issue 8 (August 1993) - Crimmins, D; Morris, J G; Walker, G L; Sue, C M; Byrne, E; Stevens, S; Jean-Francis, B; Yiannikas, C; Pamphlett, R
Abstract : The clinical manifestations of mitochondrial encephalomyopathy are described in four generations of a single kindred. The age of onset of major neurological disturbance varied from 3-70 years. In some patients, deafness was the only manifestation; in others, recurrent bouts of status epilepticus associated with focal neurological deficits and headache, caused severe disability or death. Examples of all three adult forms of mitochondrial encephalomyopathy: MELAS, MERFF and Kearns Sayre syndrome, were represented within the kindred. Associated features included deafness, short stature, non-insulin-dependent diabetes mellitus, migraine, peptic ulceration and severe constipation. The nt 3243 A-G MELAS mutation was detected in two members of the kindred. This study highlights the diversity of clinical expression of a mitochondrial mutation within a single kindred.